ナンキョク ノ キョダイ ジシン ト ナンキョク プレート ノ シンカ ニ カンスル ケンキュウ シュウカイ ホウコク - 野木, 義史; ノギ, ヨシフミ; Nogi, Yoshifumi (1999)
P(論文) 1999年2月12日に「1998年3月25日の南極地震と南極プレートの進化に関する研究集会」を行った。本研究集会は, ゴンドワナ分裂から今日までの南極プレートの進化, 現在の動き, 変形等を様々な側面から総合的に検証することにより, 1998年3月25日の南極プレート内の巨大地震を再検討し, この地震の原因にせまることを主たる目的とした。さらに, 南極プレートの研究の現状と問題点を明らかにし, これらを基に今後の研究・観測に関する議論を行った。本研究集会により, 1998年3月25日の南極巨大地震の主たる原因の候補は, 氷床変動によるアイソスタティク・リバウンドおよびプレート運動に伴うプレート内変形の二つに絞られた。 A meeting on the Antarctic great earthquake and the evolution of the Antarctic plate was held on February 12,1999. The main object of the meeting was to review the great earthquake in the Balleny Sea on March 25,1998,and study its cause from various aspects of solid earth science in the Antarctic plate, e. g. evolution since the Gondwana breakup, present motion and deformation in the Antarctic plate. Moreover, research results and problems concerning the Antarctic plate were presented and future research plans were discussed. Possible causes of the great earthquake were narrowed down to two possibilities, glacial isostatic rebound and deformation of the Antarctic Plate due to plate motion. departmental bulletin paper